Guerre juste et droit de la guerre dans l’Encyclopédie - Delia, Luigi (2010)
Guerre juste et droit de la guerre dans l’Encyclopédie (2010) 19 février 2013, par Delia, Luigi Montesquieu.it, 2 (2010), Bologna, CLUEB, p. 94-108.
Keywords: exportSPIP